2013
DOI: 10.4103/0972-0464.142389
|View full text |Cite
|
Sign up to set email alerts
|

Influence of physico-chemical parameters on the distribution of uranium in the ground water of Bangalore, India

Abstract: Laser-Induced Fluorimetry has been used to measure the concentration of uranium in the ground water samples collected from the selected study locations of Bangalore city, India. The concentration of uranium in the collected water samples is found to be in the range 0.24 μg/l to 770.1 μg/l, with a geometric mean (GM) value of 18.9 μg/l. About 35% of the water samples show the concentration of uranium above the safe limit of 30 μg/l, set by the United States Environmental Protection Agency (USEPA). The annual ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 3 publications
3
3
0
Order By: Relevance
“…Groundwater in Bengaluru had a mean concentration of 68.4 μg/L, however, the median concentration was 6.8 μg/L showing the influence of a few high outlier values (Table 1). These distributions are comparable with results from previous groundwater studies in Bengaluru by Nagaiah et al (2013) and Mathews et al (2015) which reported maximum concentrations of 770 and 2027 μg/L, and median concentrations of 20.6 and 92.4 μg/L respectively. Uranium concentrations were found to vary greatly within short distances (Fig.…”
Section: Uranium In Drinking Water and Implications For Health And Exposuresupporting
confidence: 90%
See 1 more Smart Citation
“…Groundwater in Bengaluru had a mean concentration of 68.4 μg/L, however, the median concentration was 6.8 μg/L showing the influence of a few high outlier values (Table 1). These distributions are comparable with results from previous groundwater studies in Bengaluru by Nagaiah et al (2013) and Mathews et al (2015) which reported maximum concentrations of 770 and 2027 μg/L, and median concentrations of 20.6 and 92.4 μg/L respectively. Uranium concentrations were found to vary greatly within short distances (Fig.…”
Section: Uranium In Drinking Water and Implications For Health And Exposuresupporting
confidence: 90%
“…Uranium concentrations were found to vary greatly within short distances (Fig. 6a), this corroborates similar trends reported in Nagaiah et al (2013), including the high U groundwater associated with the Bengaluru granite outcrop (Fig. 6a).…”
Section: Uranium In Drinking Water and Implications For Health And Exposuresupporting
confidence: 88%
“…The minimum uranium concentrations in the Bangalore Urban district were 0.94 (PRM) and 1.38 µg/L (POM), whereas the maximum concentrations were 98.79 (PRM) and 96.52 µg/L (POM) (Table 1). It could also be observed from the study that the uranium concentrations varied within shorter distances from the populations; this was in line with the similar tendencies that were mentioned by Nagaiah et al [41]. This made it so that the distributions of the naturally occurring uranium in the groundwaters reflected the local environments [42].…”
Section: Estimation Of Uranium With Different Water-quality Parameterssupporting
confidence: 89%
“…Unlike in northern India, no specific pattern of contamination was identified in southern India. Uranium concentrations in regions of Andhra Pradesh and Telangana were noted as sporadic, varying from extremely high (1452 μg L –1 ) to as low as 1 μg L –1 . , Similar distribution of U was observed in the states of Karnataka and Tamil Nadu. Such spatial distribution of U could likely result from U deposits in unconformities identified in proximity to the contaminated zones of these regions …”
Section: Resultsmentioning
confidence: 79%